Respon Siswa Terhadap Penggunaan Media Gambar dalam Pembelajaran IPAS (Studi Kasus) Di Kelas III SDN 14 Kelakik - Ilda Karmila; Septian Peterianus (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to examine the responses of third-grade students to the use of picture media in teaching Natural and Social Sciences (IPAS) on the topic of the characteristics of living things, focusing on motivation, active engagement, and conceptual understanding. The study employed a qualitative approach with a case study design, involving 26 students as subjects and using data collection techniques based on triangulation through observation, semi-structured questionnaires, and documentation. The results indicate that the use of picture media is highly effective in enhancing students’ understanding up to 95%, promoting active participation, and improving academic performance, as evidenced by students’ quick responses to teacher questions, success in multiple-choice exercises, and achievement of the Minimum Competency Criteria (KKM) in the Midterm Examination. Picture media can transform abstract concepts into concrete visualizations, making learning more interactive and engaging compared to conventional methods such as lectures. These findings highlight the importance of integrating picture media into the IPAS curriculum under the Merdeka Curriculum to improve the quality of learning and knowledge retention in elementary school students.